2023
DOI: 10.3389/fbioe.2023.1193424
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal co-cultivation -recent methods, trends in omic-studies, applications, and future challenges

Raseena Naseema Rasheed,
Asma Pourbakhtiar,
Malihe Mehdizadeh Allaf
et al.

Abstract: The burgeoning human population has resulted in an augmented demand for raw materials and energy sources, which in turn has led to a deleterious environmental impact marked by elevated greenhouse gas (GHG) emissions, acidification of water bodies, and escalating global temperatures. Therefore, it is imperative that modern society develop sustainable technologies to avert future environmental degradation and generate alternative bioproduct-producing technologies. A promising approach to tackling this challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 242 publications
(304 reference statements)
0
0
0
Order By: Relevance
“…In microalgae cultivation, high-concentration carbon dioxide aeration is performed to increase the growth ability of the microalgae. Therefore, the co-cultivation of microalgae and heterotrophic microorganisms is attracting attention to improve the growth of microalgae without the aeration of high-concentration carbon dioxide (Naseema Rasheed et al, 2023;Ray et al, 2022). Previous studies reported that the growth rate of microalgae increases under dilute CO2 atmospheric conditions when C. reinhardtii and Saccharomyces cerevisiae are co-cultured (Karitani et al, 2024a;Karitani et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%
“…In microalgae cultivation, high-concentration carbon dioxide aeration is performed to increase the growth ability of the microalgae. Therefore, the co-cultivation of microalgae and heterotrophic microorganisms is attracting attention to improve the growth of microalgae without the aeration of high-concentration carbon dioxide (Naseema Rasheed et al, 2023;Ray et al, 2022). Previous studies reported that the growth rate of microalgae increases under dilute CO2 atmospheric conditions when C. reinhardtii and Saccharomyces cerevisiae are co-cultured (Karitani et al, 2024a;Karitani et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%